The effectiveness of coatings when turning hardened cold work tool steel AISI D2 (60 HRC). (27th October 2008) - Mohamad, Ahmad Kamely; Yusof, Noordin Mohd; Ourdjini, Ali; Venkatesh, Vellore Chelvaraj
Studies have shown that by using the right combination of insert tool geometry and cutting parameters, hard turning can produce a better surface finish compared to the grinding process. The development of new cutting tools and improvements in machine tool rigidity provides a very competitive alternative to grinding. Newly developed turning grades are intended to permit versatile use in roughing and finishing applications for a broader spectrum of workpiece materials. The technological improvements in coatings make hard turning more feasible and its use has widely expanded. Today, the industry has a strong interest in multicomponent coatings, combining wear-resistance with a low coefficient of friction. In this study, the effectiveness of multilayer TiN/AI2O3/TiCN CVD coating was compared to TiAIN PVD coating when hard turning AISI D2 cold work tool steel of 60 HRC based on the tool life, tool wear, surface finish and chip morphology. Results show that low content CBN coated with TiN/AI2O3/TiCN and TiAlN showed similar tool life and that all types of coatings investigated failed by abrasion and plastic deformation. Both coated and uncoated cutting tools were found to produce good surface finish.